A System Dynamics Approach to Analysing the Effect of Clientelism on Public Organizations Performance in Italy - Federico COSENZ (Revista de Management Comparat International)
This paper tries to analyse the effects of political clientelism on the performance of public utilities and organizations in Italy. Shortly, clientelism consists in a series of reciprocal convenience-based relationships between politicians and individuals, commanding unequal resources and involving mutually beneficial transactions in terms of economic, social and political consequences. The motivation of this research stems from the fact that analysing the effect of clientelism may contribute in (1) improving the quality of electoral strategies and the resulting public policies and (2) managing the performance of public organizations according to a sustainable perspective. Hence, the key issues of the paper are the following: is clientelism a sustainable mechanism to enlarge the consensus of a given party? How does clientelistic practice impact on public organizations management and subsequent performances? What should public managers do to limit the effect of clientelism and maintain satisfying performance results in providing services towards citizens? In the light of the above questions, the paper points out the cause-and-effect relations among those variables underlying such clientelistic practices by using a System Dynamics approach which allows one to frame a complex system and understand its development over time.